Carga mental de trabajo en enfermeras/os de unidades de paciente crítico: estudio piloto - Ceballos-Vásquez, Paula Andrea (Universidad de Sonora, 2019)
Objective: To determine the perception of mental workload on nurses as a critical care unit of a Regional Hospital in Chile. Methods: descriptive study, transverse and exploratory design. 10 nurses were censused who work in a turn of the Critical Patient Unit of the Regional Hospital of Chile. Scale of Subjective Mental Workload and bio/psycho/ socio/demographic background: To collect data two instruments were used. To carry out this study, the Emanuel E. ethical requirements were considered. Results: average 3.8 (SD = 66) workers / UPC as a participant in this study, perceived mental workload when performing their work. Conclusion: Mental work overload, could generate consequences for their physicaland mental health of nurses / participants, making it a priority to take measures to maintain adequate mental burden.